The Value of Wi-Fi as Entertainment: An Application to Free Wi-Fi in City Buses of Korea - Yongwon Kim; Yongkyu Kim (International Telecommunications Society (ITS), 2020)
As the usage of mobile data is significantly increasing, the demand for free public Wi-Fi also continues to grow. The ministry of science & ICT (MSIT) and some municipalities in Korea have been constructing free Wi-Fi networks on mass transportation for the benefit of users. In this study, we estimate the economic value of Wi-Fi for leisure based on demand function, which considers the time cost of using the internet. By using the 2016-2019 Korean Media Panel (KMP) data, we estimated the yearly consumer surplus of Wi-Fi and that of Wi-Fi in city buses. In this way, we showed the cost-benefit analysis could be carried out in public Wi-Fi projects.
Keywords: 330; Wi-Fi; Internet; Consumer Surplus; Panel Analysis